Epidemiologic Risk, Influenza Subtype, Clinical Severity and Viral Shedding as a Function of Baseline Influenza A Viral Load. (4th October 2017) - Schofield, Christina; Chen, Wei-Ju; Fairchok, Mary; Maves, Ryan; Arnold, John; Danaher, Patrick; Deiss, Robert; Lalani, Tahaniyat; Rajnik, Michael; Burgess, Timothy; Millar, Eugene; Coles, Christian
Abstract: Background: Higher baseline influenza viral load (BVL) in nasopharyngeal (NP) secretions is associated with prolonged hospitalization in co-morbid patients. The association between BVL and clinical outcomes in otherwise healthy populations is poorly defined. Methods: The Acute Respiratory Infection Consortium (ARIC) is a multi-site network at five military medical centers in the US. Healthy children and adults <65y presenting within 72 hours of ILI onset were prospectively enrolled in an observational cohort study. Viral etiologies and shedding were determined by serial nucleic acid amplification testing of NP swabs. Influenza BVL was determined by comparison of influenza-specific quantitative PCR assays (qPCR) against two housekeeping gene qPCR assays. Demographics, clinical data and self-reported symptom severity of 20 symptoms were ascertained at baseline. Results: 55 enrollees (24 pH1N1 and 31 H3N2) had BVL data available for analysis. In patients aged 18–30 BVL correlated with age (increased 0.17 log10 copies/mL per year, P = 0.03). For those > 30 years, BVL decreased with age (0.05 log10 copies/mL per year, P = 0.06). There was no association with gender, ethnicity or BMI. There was no difference in median BVL between subtypes (H1N1 6.11 log10 copies/mL vs H3N2 6.44; P = 0.33). Higher mean BVL (6.24 log10 copies/mL vs. 5.48; P = 0.02) was associated with higher rate of reported chills, but not with other symptoms. Mean BVL trended lower among inpatients ( P = 0.128), although inpatients received antivirals at higher rates than outpatients (3/4 vs 4/47; P = 0.005). Patients prescribed antivirals had a non-significant lower BVL than nonusers. Cases that received influenza vaccine during the year of enrollment trended toward higher BVL ( P = 0.104). Higher BVL was associated with increased rates of viral shedding at day 0 and 3, but not day 7 (RR=1.71; 95% CI 1.04, 2.80). Conclusion: Higher influenza BVL was associated with higher rate of self-reported chills, but not other clinical severity measures. Age was positively correlated with BVL until age 30 after which there was a negative correlation. Influenza subtype and use of antivirals did not impact BVL; however, current vaccination trended toward increased BVL. Higher baseline BVL was associated with increased rates of viral shedding. Disclosures: All authors: No reported disclosures.